"Nature is our true friend": the environmental empathy of a modern female guru in North India - DeNaploi, Antoinette (Nidān, 2016)
This article describes and analyzes the rhetorical performances (dharm-kathās) of a modern female Hindu renouncer (sādhu), who is affectionately called Guru Ma, in order to spotlight a cultural phenomenon which is characterized as "experimental Hinduism", and which is evident in Guru Ma's performance of narrative to reformulate dharm through the frame of environmental empathy in her public dharm-kathā events. Based on extensive ethnographic research conducted in North India with Guru Ma and her community between 2013 and 2015, this article suggests that Guru Ma performs a new meaning of dharm that foregrounds environmental empathy and the moral agency of nature. Through her performances, Guru Ma constructs nature as an intelligent and compassionate moral agent of dharm, which embodies the expanding moral consciousness and power of the divine Absolute. Her performances also work to evoke ecological change in her community and interrogate late modern capitalism's ideal of unfettered material consumption as illustrative of "the good life".